Drought events determine performance of Quercus ilex seedlings and increase their susceptibility to Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Juárez, Enrique; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2014)
More frequent weather extremes are expected to occur in the Mediterranean region within the present context of climate change. These extremes could affect forests and plant diseases driven by pathogens. It is hypothesised that simulation of weather extremes during Quercus ilex growth will influence early performance and susceptibility to the invasive oomycete Phytophthora cinnamomi. In 2010, 140 Q. ilex seedlings were subjected to three watering regimes under greenhouse conditions: waterlogging (W), water stress (S) and optimal watering regime for growth (C). During the second vegetative period, conditions were altered to create the following scenarios: WW, WS, SS, SW and CC. After the second vegetative period, plants were artificially infested with P. cinnamomi. Holm oak (Q. ilex) was more sensitive to flooding in the first year of growth than in the second year. The altered scenarios produced plants with a lower fine-to-total root ratio than plants in unaltered scenarios. Plants with the highest growth rates maintained their relatively rapid growth and photosynthetic activity under altered scenarios. However, plants with the highest growth rates became the plants with the lowest growth rates when two consecutive years of drought occurred, indicating a trade-off by Q. ilex in growth investment, observed only if the water stress scenario persists. Seedlings were more sensitive to water shortage than to waterlogging, especially if they encountered a dry scenario during the first year. Exposure to drought events increased seedling mortality rates after P. cinnamomi infection. Waterlogging combined with subsequent water deprivation was the worst scenario when soil was infested with P. cinnamomi, causing 100% mortality of plants.
Keywords: climate change; Drought; Flooding; Invasive pathogen; Oak decline; Weather extremes